Meningkatkan Antusiasme Belajar Siswa pada Pelajaran Sejarah Kebudayaan Islam Melalui Metode Role Playing - Nur Azizatul Haqiah; Rofiatus Sa’adah; Aufa Fatchia Rahma; Fadhilla Putri; Sibawaihi Sibawaihi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The present research investigates whether the implementation of role-playing can enhance learners’ enthusiasm for Islamic Cultural History (SKI) at MI Al-Huda. The study was motivated by observed declines in student interest and engagement attributed to traditionally teacher-centered instructional practices. Adopting a qualitative descriptive framework, the researcher obtained information through classroom observations, semi-structured interviews, and documentary evidence. To ensure the credibility of findings, the study employed triangulation across data sources, collection techniques, and temporal periods. The findings indicate that applying the role-playing method effectively increased students’ enthusiasm for learning. Learners became more active, confident, and motivated to participate in SKI activities. The method also fostered positive social interaction, cooperation, and a sense of responsibility among students. Its main advantage is the creation of an engaging, contextual, and enjoyable learning atmosphere, while its limitation lies in the extended time required and limited school facilities. Overall, the role-playing method proved effective as an alternative strategy for promoting interactive and meaningful SKI learning.